PENGARUH ASPEK AFEKTIF DAN PSIKOMOTOR DALAM PEMBELAJARAN PENDIDIKAN JASMANI TERHADAP KESEHATAN SISWA: ANALISIS SEM-PLS - Karisdha Pradityana (STKIP Melawi, 2026)
Abstract: This study aims to analyze the influence of affective and psychomotor aspects in physical education learning on student health through the Partial Least Square Structural Equation Modeling approach. The research design used a quantitative survey method with a five-point Likert scale questionnaire instrument consisting of 12 statements. The research sample was school students who participated in physical education learning. Data were analyzed using SmartPLS with the stages of measurement model testing and structural model testing. The results showed that all constructs were valid and reliable with an AVE value of >0.5 and Composite Reliability >0.7. The R² value of student health was 0.704 which is categorized as strong. Bootstrapping analysis revealed that affective (p = 0.000) and psychomotor (p = 0.001) aspects had a significant positive effect on student health. These findings confirm that physical education that emphasizes both affective and psychomotor aspects can make a real contribution to improving student health. Physical education teachers should foster positive attitudes and vary physical activities so that students become healthy and fit. Keywords: Physical Education; Affective; Psychomotor; Student Health; SEM-PLS. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh aspek afektif dan psikomotor dalam pembelajaran pendidikan jasmani terhadap kesehatan siswa melalui pendekatan Partial Least Square Structural Equation Modeling. Desain penelitian menggunakan metode survei kuantitatif dengan instrumen kuesioner skala Likert lima poin yang terdiri atas 12 butir pernyataan. Sampel penelitian adalah siswa sekolah yang mengikuti pembelajaran pendidikan jasmani. Data dianalisis menggunakan SmartPLS dengan tahapan uji model pengukuran dan uji model struktural. Hasil penelitian menunjukkan bahwa semua konstruk valid dan reliabel dengan nilai AVE >0,5 dan Composite Reliability >0,7. Nilai R² kesehatan siswa sebesar 0,704 yang termasuk kategori kuat. Analisis bootstrapping mengungkapkan bahwa aspek afektif (p = 0,000) dan psikomotor (p = 0,001) berpengaruh positif signifikan terhadap kesehatan siswa. Temuan ini menegaskan bahwa pendidikan jasmani yang menekankan aspek afektif maupun psikomotor dapat memberikan kontribusi nyata dalam meningkatkan kesehatan siswa. Guru PJOK sebaiknya menumbuhkan sikap positif dan memvariasikan aktivitas fisik agar siswa menjadi sehat dan bugar. Kata Kunci: : Pendidikan Jasmani; Afektif; Psikomotor; Kesehatan Siswa; SEM-PLS.